Catabolic and regulatory systems in Shewanella oneidensis MR-1 involved in electricity generation in microbial fuel cells - Kouzuma, Atsushi; Kasai, Takuya; Hirose, Atsumi; Watanabe, Kazuya (Frontiers in Microbiology, 2015)
Shewanella oneidensis MR-1 is a facultative anaerobe that respires using a variety of inorganic and organic compounds. MR-1 is also capable of utilizing extracellular solid materials, including anodes in microbial fuel cells (MFCs), as electron acceptors, thereby enabling electricity generation. As MFCs have the potential to generate electricity from biomass waste and wastewater, MR-1 has been extensively studied to identify the molecular systems that are involved in electricity generation in MFCs. These studies have demonstrated the importance of extracellular electron-transfer pathways that electrically connect the quinone pool in the cytoplasmic membrane to extracellular electron acceptors. Electricity generation is also dependent on intracellular catabolic pathways that oxidize electron donors, such as lactate, and regulatory systems that control the expression of genes encoding the components of catabolic and electron-transfer pathways. In addition, recent findings suggest that cell-surface polymers, e.g., exopolysaccharides, and secreted chemicals, which function as electron shuttles, are also involved in electricity generation. Despite these advances in our knowledge on the extracellular electron-transfer processes in MR-1, further efforts are necessary to fully understand the underlying intra- and extra-cellular molecular systems for electricity generation in MFCs. We suggest that investigating how MR-1 coordinates these systems to efficiently transfer electrons to electrodes and conserve electrochemical energy for cell proliferation is important for establishing the biological bases for MFCs.